The Development of Learning Media of Pakakala Boardgame - Hasan, Kamaruddin; Zainal, Zaid; Suhadjerah, Suhadjerah (Journal of Educational Science and Technology (EST), 2020)
The purpose of this study is to develop a learning media in the form of boardgame Learning Media (Optional Board and Career Cards) to improve students’ career knowledge in a fun, interactive and active learning under. This research uses Research and Development Method, with The phases in this research consist of; (1) product analysis, (2) developing products, (3) validation and revision, (4) play-trials and final products. Data collection techniques using interviews and questionnaires. Feasibility check and assessment by theory expert, learning media expert and users using Likert scale with the value used are 5 to 1. The results of the validation by theory expert get score 5 with a very worthy category, while the validation by media expert gets score 4.89 with the very worthy category. Whereas in the usage test by users or students and teacher response as an education practitioner showed very worthy category with scores 4.53 and 5 respectively. As a result, the developed pakakala boardgame for year 4 students at SDN 84 Parepare is suitable to use in teaching theme 4 concerning various occupations